Hubungan Strategi dan Media Pembelajaran dengan Minat Belajar Sejarah Kebudayaan Islam Kelas VIII di MTsN 1 Kota Bukittinggi - Indah Permata Sari; M Arif; Khairuddin Khairuddin; Diyan Permata Yanda (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This research was motivated by the discovery of several problems faced by students, namely poor interest in learning, such as the level of activeness of students during the learning process and low interest of students in SKI learning. Students felt that in this learning there was no passion or interest, as indicated by students being less active in the learning process and student involvement in the SKI learning process also decreased. With these conditions, students quickly get bored and are not interested in participating in learning. As a result, difficulties arise that affect the learning objectives to be achieved. This study aims to determine the relationship between learning strategies and learning media with interest in learning Islamic Cultural History class VIII at MTsN 1 Bukittinggi. The type of research used in this research is quantitative, correlational. The population is all class VIII students with a total of 347 students spread across 11 classes. The sample in this research used the Probability Sampling technique using Simple Random Sampling, and the total research sample was 78 students. Data was collected through questionnaires, observation and documentation analyzed using normality tests, linearity tests, multiple correlation analysis and hypothesis testing. Based on the results of the research that has been done, the results show that there is a relationship between learning strategies on student interest in learning in the subject of Islamic Culture History class VIII at MTsN 1 Bukittinggi City and the relationship between learning media on student interest in learning in the subject of Islamic Culture History class VIII at MTsN 1 Bukittinggi City, as evidenced by the results of the Pearson Product Moment correlation test on the relationship between learning strategies and interest in learning with a Pearson correlation value of 0.382 and a significant value of 0.001 <0.05. While the Pearson correlation test results on the relationship between learning media and interest in learning are 0.236 with a significant value of 0.038 <0.05. Furthermore, the results of the Pearson correlation test on the relationship between learning strategies and media with learning interest are <0.05, which is certainly valid and related. Based on this value, it can be seen that the relationship between learning strategies to interest in learning is interconnected and the relationship between learning media to interest in learning is interconnected, so Ha is accepted.